COMPARISON OF THE EFFICACY OF ANTIBIOTIC-STEROID AND ICHTHAMMOL GLYCERINE WICK IN TREATMENT OF ACUTE OTITIS EXTERNA - Khan, Maryam; Butt, Kamran Ashfaq Ahmed; Riaz, Naeem; Hassan, Zaheer Ul; Ahmed, Attique; Wasif, Muhammad (Pakistan Armed Forces Medical Journal, 2021)
Objective: To compare the efficacy of steroid antibiotic wick with Ichthammol Glycerol wick in the management of Acute Otitis Externa in terms of tenderness and clearance of discharge/debris. Study Design: Quasi-experimental study. Place and Duration of Study: ENT Out Patient department of Combined Military Hospital Peshawar and Hayatabad Medical Complex Peshawar, from May to Nov 2018. Methodology: A total of 250 patients were included and divided into two groups of 125 each. After necessary suction clearance topical Ciprofloxacin/Dexamethasone (Cipotec-D) wick was placed in auditory canal of group A patients and topical Glycerol/Ichthammol wick was placed in group B. Follow up visits were done on 3rd and 7th day of starting the treatment. Results: Group A patients responded better in terms of tenderness (88%) however both groups had similar response in terms of discharge reduction (7.2% vs 6.4%). In terms of efficacy neither of the treatment proved more efficacious compared to the other (p-value 0.058). Conclusion: While steroid antibiotic wick is significantly more efficient in terms reducing tenderness, in terms of overall efficacy and discharge reduction Ichthammol/glycerol is equally effective.